Sperm Transcripts Associated With Odorant Binding and Olfactory Transduction Pathways Are Altered in Breeding Bulls Producing Poor-Quality Semen - Karuthadurai, Thirumalaisamy; Das, Dayal Nitai; Kumaresan, Arumugam; Sinha, Manish Kumar; Kamaraj, Elango; Nag, Pradeep; Ebenezer Samuel King, John Peter; Datta, Tirtha Kumar; Manimaran, Ayyasamy; Jeyakumar, Sakthivel; Ramesha, Kerekoppa (Frontiers in Veterinary Science, 2022)
Spermatozoa carries a reservoir of mRNAs regulating sperm functions and fertilizing potential. Although it is well recognized that a considerable proportion of high genetic merit breeding bulls produce poor quality semen, the transcriptomic alterations in spermatozoa from such bulls are not understood. In the present study, comparative high-throughput transcriptomic profiling of spermatozoa from good and poor-quality semen producing bulls was carried out to identify the transcripts associated with semen quality. Using Next Generation Sequencing (NGS), we identified 11,632 transcripts in Holstein Friesian bull spermatozoa; after total hit normalization, a total of 544 transcripts were detected, of which 185 transcripts were common to both good and poor-quality semen, while 181 sperm transcripts were unique to good quality semen and 178 transcripts were unique to poor quality semen. Among the co-expressed transcripts, 31 were up-regulated while 108 were down regulated and 46 were neutrally expressed in poor quality semen. Bioinformatics analysis revealed that the dysregulated transcripts were predominantly involved in molecular function such as olfactory receptor activity and odour binding, and in biological process such as detection of chemical stimulus involved in sensory perception, sensory perception of smell, signal transduction and signal synaptic transmission. Since a majority of the dysregulated transcripts were involved in olfactory pathway (85% of enriched dysregulated genes were involved in this pathway), the expression of selected five transcripts associated with this pathway (OR2T11, OR10S1, ORIL3, OR5M11, and PRRX1) were validated using real time qPCR, and found that their transcriptional abundance followed the same trend as observed in NGS; the sperm transcriptional abundance of OR2T11 and OR10S1 differed significantly (p<0.05) between good and poor quality semen. It is concluded that poor quality semen showed altered expression of transcripts associated with olfactory receptors and pathways indicating the relationship between olfactory pathway and semen quality in bulls.